FORECASTING SYSTEM FOR PASSENGER, AIRPLANE, LUGGAGE AND CARGO, USING ARTIFICIAL INTELLIGENCE METHOD - BACKPROPAGATION NEURAL NETWORK AT JUANDA INTERNATIONAL AIRPORT - lady silk moonlight; Achmad Setiyo Prabowo (Research and Development Agency of The Ministry of Transportation, 2019)
Juanda International Airport is the third busiest airport, after Soekarno Hatta International Airport and Ngurah Rai International Airport. Because the number of Airplane, passengers, luggage and cargo at Juanda International Airport is increasing every year, it is important to improve infrastructure facilities and services, and all facilities at Juanda Airport. In this research, it was designed and built a forecasting system for Airplane, passenger, luggage and cargo. This research is expected to be a consideration in increasing the readiness of infrastructure and services, and all facilities at Juanda Airport. In addition, this system is also expected to be one of the decision supporting system for the management. This system uses one of the Artificial Intelligent methods, Backpropagation Artificial Neural Network. It is known in previous research that Backpropagation is a method of artificial neural networks with the best performance in pattern recognition, or forecasting. The forecasting system has two main processes, the training process and the forecasting process.